Comparison Of Depreciation According To Sak And Tax Law At Pt. Nurindo Pratama Logistik And Its Impact On Taxable Income (PKP) - Aristantya, Aura Dian; Nasrullah, Nasrullah; Bahri, Syamsul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to determine the comparison of depreciation according to SAK and Tax Law at Pt. Nurindo Pratama Logistik and its effect on Taxable Income (PKP). The author wants to find out and understand how the Depreciation Calculation according to SAK with taxation and how it affects or impacts PKP. The method used is a qualitative method with secondary data, namely data in the form of income financial statements and a list of depreciation of fixed assets at Pt. Nurindo Pratama Logistik. The results showed that the calculation of depreciation expense from the two methods, namely the depreciation method according to SAK and taxation (fiscal) in 2019, caused a difference of IDR 17,084,950.00, causing a negative fiscal correction, due to Pt. Nurindo Pratama Logistik determines a useful life of 5 years while the tax law provides a useful life of 4 years. The calculation of depreciation expense from the two methods, namely the depreciation method according to SAK and taxation (fiscal) in 2020, caused a difference of IDR 15,623,842.50, causing a negative fiscal correction, due to Pt. Nurindo Pratama Logistik determines a useful life of 5 years while the tax law provides a useful life of 4 years. The calculation of depreciation expense from the two methods, namely the depreciation method according to SAK and taxation (fiscal) in 2021, caused a difference of IDR 16,724,650.00, causing a negative fiscal correction, due to Pt. Nurindo Pratama Logistik determines a useful life of 5 years while the tax law provides a useful life of 4 years.